Effect or Span Depth Ratio on the Bending Properties of Particle Boards - Sekhar, A. C.; Gulati, A. S. (Indian Forester, 1976)
Easto-plastic materia1 like wood and wood products exhibit variation in the basic mechanical properties due to size and shape of the test specimen. Effect of span-depth ratio is a very impartant factor, because it has got a marked influence on the mechanical properties in bending tests. In the present study an attempt has been made to study the effect of span depth ratio on the mechanical properties viz. "Modulus of rupture" and "Modulus of elasticity" in bending of different qualities of commercial particle boards. It has been observed in general that optimum condition in all the cases is reached at aboat a span-depth ratio or 02, and beyond which the result are likely to be lower.